Analysis of Mathematical Critical Thinking Skills using Differentiation Learning on Junior High School Students based on Learning Style - Delina, Delina; Afrilianto, M. ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
Critical thinking skills are one of the level thinking skills, critical thinking is also no less important for students to master. In fact, students experience difficulties in developing mathematical critical thinking skills, this can be seen from students' learning outcomes which are not yet optimal. From this statement, researchers conducted research on students' mathematical critical thinking abilities. This research aims to analyze students' mathematical critical thinking abilities by using differentiation learning for junior high school students on algebra material. Differentiated learning is a learning strategy recommended by the government to support the implementation of an independent curriculum. The subjects of this research were 30 seventh grade students in junior high school in Purwakarta. This research uses a descriptive method with a qualitative approach. The stages in this research are planning, implementation and reporting. The test is given 5 questions according to indicators of critical thinking abilities. Before taking the test, students are first asked questions about their learning style. The results of the mathematical critical thinking ability test with differentiated learning show that 63% of students with a visual learning style are able to check the truth of an argument, 39% of students with a kinesthetic learning style can formulate questions with reasons, 37% of students with a visual learning style are able to identify relevant data, 38% of students with a visual learning identifies assumptions, 35% of kinesthetic learning styles are able to solve problems. Students' mathematical critical thinking abilities vary according to students' learning styles and other learning needs. It can be concluded that mathematical critical thinking abilities are influenced by differentiated learning.